Probing potential priming: Defining, quantifying, and testing the causal priming effect using the potential outcomes framework - Chén, Oliver Y.; Phan, Huy; Cao, Hengyi; Qian, Tianchen; Nagels, Guy; de Vos, Maarten (Frontiers in Psychology, 2022)
Having previously seen an item helps to uncover the item another time, given a perceptual or cognitive cue. Oftentimes, however, it may be difficult to quantify or test the existence and size of a perceptual or cognitive effect in general and a priming effect in particular. This is because to examine the existence of, and, quantify, the effect, one needs to compare two outcomes: the outcome had one previously seen the item vs. the outcome had one not seen the item. But only one of the two outcomes is observable. Here, we argue that the potential outcomes framework is useful to define, quantify, and test the causal priming effect. To demonstrate its efficacy, we apply the framework to study the priming effect using data from a between-subjects study involving English word identification. Additionally, we show that what has been used intuitively by experimentalists to assess the priming effect in the past has a sound mathematical foundation. Finally, we examine the links between the proposed method in studying priming and the multinomial processing tree (MPT) model, and how to extend the method to study experimental paradigms involving exclusion and inclusion instructional conditions.